Induced Human Intestinal Organoids (iHIOs) as Model Systems for Chemotherapy-associated Clostridium difficile (CD) Infections. (4th October 2017) - Apewokin, Senu; Pradhan, Suman; Frerick, Michael; Weiss, Alison
Abstract: Background: Patients undergoing cytotoxic chemotherapy are ten times more likely to develop Clostridium difficile infections (CDI) than the general patient population. Efforts to outline pathophysiologic mechanisms underlying this disproportionate incidence have been limited by the lack of disease-representative experimental models. We hypothesized that iHIOs could serve as toxicity models to evaluate chemotherapy-associated CDI Methods: Intact iHIOs were exposed to cytotoxic chemotherapy (melphalan) in gut media at therapeutic doses (9 μg/mL; which is the equivalent of 140 mg/m 2 human dose). Cellular death was assessed by accumulation of the membrane permeant dye, Sytox-orange added at 5-days post treatment. iHIOs were also exposed to CD toxin A and B (TcdA and TcdB respectively) and epithelial barrier damage assessed by actin mislocalization and loss of E-cadherin. For controls iHIOs were exposed / microinjected with saline/PBS. Morphological and histological changes were then captured using light and confocal microscopy Results: Morphologic and histologic assessments demonstrated cell death and epithelial barrier damage Conclusion: iHIOs demonstrate cell death on exposure to CD toxins and melphalan chemotherapy. These properties could be harnessed in establishing toxicity models for evaluation of chemotherapy-associated CDI Disclosures: S. Apewokin, T2 biosystems: Investigator, Research support Astellas: Scientific Advisor, Consulting fee